Collaborative management of severe periodontal-endodontic lesion with intense lip sucking: a case report - Yanfei Sun; Xiaofang Zhao; Mingchao Wang; Xiangkun Sun; Kunzhou Mei; Yameng Zhang; Yanwen Cui; Fang Yang (BMC Oral Health, 2025)
Abstract Background Lip behaviors can lead to maxillofacial developmental disorders such as anterior open bite, posterior crossbite, increased overjet, and a higher risk of developing a Class II malocclusion. However, lip-sucking, a behavior often underreported and overlooked, may adversely affect the periodontal health of permanent teeth in adolescents under extreme conditions if not promptly identified and managed. Case presentation We report a unique case of an 11-year-old boy with a severe periodontal-endodontic lesion on tooth 32, caused by prolonged, high-frequency, and high-intensity lip sucking. Initial clinical examination revealed gingival recession, Grade III mobility, deep periodontal pocket, and alveolar bone loss without obvious pathogenesis. The therapeutic schedule encompassed behavioral modification, the repeated application of various dental splints due to splint breakage caused by strong lip-sucking habits, and root canal therapy. The periodontal condition and tooth stability were improved through collaborative management. At the 18-month follow-up, improvements in dental stability, alveolar bone density, and reduced periodontal pocket depth were observed. Conclusions This is the first case report exploring the complex relationship between lip-sucking and dental health, emphasizing that severe oral habits can lead to serious dental consequences. Timely identification and intervention in managing oral habits can halt disease progression and ensure favorable outcomes. Additionally, this report offers treatment guidelines and recommendations for severe dental diseases caused by detrimental oral habits.